Iron and silicon isotope behaviour accompanying weathering in Icelandic soils, and the implications for iron export from peatlands. (15th November 2017) - Opfergelt, S.; Williams, H.M.; Cornelis, J.T.; Guicharnaud, R.A.; Georg, R.B.; Siebert, C.; Gislason, S.R.; Halliday, A.N.; Burton, K.W.
Abstract: Incipient warming of peatlands at high latitudes is expected to modify soil drainage and hence the redox conditions, which has implications for Fe export from soils. This study uses Fe isotopes to assess the processes controlling Fe export in a range of Icelandic soils including peat soils derived from the same parent basalt, where Fe isotope variations principally reflect differences in weathering and drainage. In poorly weathered, well-drained soils (non-peat soils), the limited Fe isotope fractionation in soil solutions relative to the bulk soil (Δ 57 Fesolution-soil = −0.11 ± 0.12‰) is attributed to proton-promoted mineral dissolution. In the more weathered poorly drained soils (peat soils), the soil solutions are usually lighter than the bulk soil (Δ 57 Fesolution-soil = −0.41 ± 0.32‰), which indicates that Fe has been mobilised by reductive mineral dissolution and/or ligand-controlled dissolution. The results highlight the presence of Fe-organic complexes in solution in anoxic conditions. An additional constraint on soil weathering is provided by Si isotopes. The Si isotope composition of the soil solutions relative to the soil (Δ 30 Sisolution-soil = 0.92 ± 0.26‰) generally reflects the incorporation of light Si isotopes in secondary aluminosilicates. Under anoxic conditions in peat soils, the largest Si isotope fractionation in soil solutions relative to the bulk soil is observed (Δ 30 Sisolution-soil = 1.63 ± 0.40‰) and attributed to the cumulative contribution of secondary clay minerals and amorphous silica precipitation. Si supersaturation in solution with respect to amorphous silica is reached upon freezing when Al availability to form aluminosilicates is limited by the affinity of Al for metal–organic complexes. Therefore, the precipitation of amorphous silica in peat soils indirectly supports the formation of metal–organic complexes in poorly drained soils. These observations highlight that in a scenario of decreasing soil drainage with warming high latitude peatlands, Fe export from soils as Fe-organic complexes will increase, which in turn has implications for Fe transport in rivers, and ultimately the delivery of Fe to the oceans.